2020
DOI: 10.1007/s12369-020-00678-1
|View full text |Cite
|
Sign up to set email alerts
|

“THIS ISN’T ME!”: The Role of Age-Related Self- and User Images for Robot Acceptance by Elders

Abstract: Although companion-type robots are already commercially available, little interest has been taken in identifying reasons for inter-individual differences in their acceptance. Elders’ age-related perceptions of both their own self (self-image) and of the general older robot user (user image) could play a relevant role in this context. Since little is known to date about elders’ companion-type robot user image, it is one aim of this study to investigate its age-related facets, concentrating on possibly stigmatiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Most of the included articles involved quantitative data collection methods using various constructs and questionnaires. e acceptance of SARs was primarily assessed by constructing technology acceptance models to compile questionnaires [12,14,18,22,23,25,26,29,31,37,40,42,45,47]. Furthermore, self-developed questionnaires were also used [19,20,27,41,43,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included articles involved quantitative data collection methods using various constructs and questionnaires. e acceptance of SARs was primarily assessed by constructing technology acceptance models to compile questionnaires [12,14,18,22,23,25,26,29,31,37,40,42,45,47]. Furthermore, self-developed questionnaires were also used [19,20,27,41,43,46].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Kodate et al, about 178 (77%) of respondents reported that they were open to the use of home-care robots [40]. e three other studies reported that older adults had negative attitudes towards the idea of SARs in aged care [15,29,47]. Furthermore, they showed low intentions to use the robot.…”
Section: General Attitudes Towards Using Sarsmentioning
confidence: 99%
“…Participation was contingent on (a) having completed >50 surveys with a minimal HIT approval rate of 98% or greater, (b) being located in either the USA, UK, Canada, Ireland, Australia, or New Zealand, and (c) having no experience with robotics and/or any expertise in AI (e.g., data science and machine learning). It should be noted here, that both technical expertise and experience with robotics, have been found consistently to predict favorable responses toward, and acceptance of, social robots [e.g., 23,65,26,63,107,62,96]. Thus, it seemed reasonable to exclude such individuals as they may have obscured our findings.…”
Section: Recruitmentmentioning
confidence: 80%
“…As shown in Appendix Table A1, we collected 20 papers published from 2017 to 2020 about user acceptance of service robots. These studies used theories including TAM (Hwa et al., 2018; Saadatzi et al., 2020), UTAUT (Guggemos et al., 2020; Kencebay, 2019), DIT (Khaksar et al., 2019), Attribution Theory (Belanche et al., 2020), Self‐Congruity Theory (Dudek et al., 2020), and Uncanny Valley Theory (Appel et al., 2020). Based on TAM/UTAUT, relevant studies have also created new models, such as RAM (Turja et al., 2019), HRCAM (Bröhl et al., 2019), an AIDUT (Lin et al., 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%